Synthesis of Chiral 1, 4‐Benzodioxanes and Chromans by Enantioselective Palladium‐Catalyzed Alkene Aryloxyarylation Reactions. (15th March 2016) - Hu, Naifu; Li, Ke; Wang, Zheng; Tang, Wenjun
Abstract: A highly enantioselective alkene aryloxyarylation led to the high‐yielding formation of a series of 1, 4‐benzodioxanes, 1, 4‐benzooxazines, and chromans containing quaternary stereocenters with excellent enantioselectivity. The sterically bulky and conformationally well defined chiral monophosphorus ligandL4 orL5 was responsible for the high reactivity and enantioselectivity of these transformations. The application of this method to the synthesis of the chiral chroman backbone of α‐tocopherol was demonstrated.